Development of heavy metal potentiostat for batik industry - Umar, S.N.H. (MDPI AG, 2020)
The consumption of reactive dyes in the batik industry has led to a severe concern in monitoring the heavy metal level in wastewater. Due to the necessity of implementing a wastewater monitoring system in the batik factory, a Heavy Metal potentiostat (HMstat) was designed. The main goal of this study is to understand the optimal design concept of the potentiostat function in order to investigate the losses of accuracy in measurement using off-the-shelf devices. Through lab-scale design, the HMstat comprises of an analog potentiostat read-out circuit component (PRCC) and a digital control signal component (CSC). The PRCC is based on easy to use components integrated with a NI-myRIO controller in a CSC. Here, the myRIO was equipped with built-in analog to digital converter (ADC) and digital to analog converter (DAC) components. In this paper, the accuracy test and detection of cadmium(II) (Cd2+) and lead(II) (Pb2+) were conducted using the HMstat. The results were compared with the Rodeostat (an open source potentiostat available on the online market). The accuracy of the HMStat was higher than 95 and within the precision rate of the components used. The HMstat was able to detect Cd2+ and Pb2+ at â0.25 and â0.3 V, respectively. Similar potential peaks were obtained using Rodeostat (Cd2+ at â0.25 V and Pb2+ at â0.3 V). Â© 2020 by the authors. Licensee MDPI, Basel, Switzerland.